HrHPV testing vs liquid-based cytology in cervical cancer screening among women aged 50 and older: a prospective study. Issue 11 (9th October 2020) - Andersen, Berit; Njor, Sisse Helle; Jensen, Anne Marie Schak; Johansen, Tonje; Jeppesen, Ulla; Svanholm, Hans
Abstract : Introduction: Evidence supports high-risk human papilloma virus (HPV) testing as the primary cervical cancer screening tool. However, benefits and harms should be carefully considered before replacing liquid-based cytology. In women age 50 and older, we evaluated how a commercially available DNA amplification HPV test compares with routine liquid-based cytology. Methods: This prospective study included 4043 patients who had a cervical sample analyzed from September 2011 to September 2012. Patients were followed between 64 and 76 months (median: 70 months). Samples were analyzed using both liquid-based cytology and the Cobas 4800 HPV DNA test. We calculated the diagnostic efficacy of liquid-based cytology and HPV, with or without the opposite test as triage, using cervical intraepithelial neoplasia (CIN2+/CIN3+) as reference. Results: The patients had a median age of 58 years, (range; 50–90). At baseline, HPV prevalence was 8.0%: a total of 3.7% of patients had atypical squamous cells of undetermined significance or worse (ASCUS+). Positive test results were 1.9% for liquid-based cytology with HPV triage and 3.0% for HPV with liquid-based cytology triage. The cumulative incidence of CIN3+ was 1.0% (40/4043). Sensitivities for CIN3+ were: liquid-based cytology 47.5% (31.5%–63.9%); liquid-based cytology with HPV triage 45.0% (29.3%–61.5%); HPV 90.0% (76.3%–97.2%); and HPV with liquid-based cytology triage 67.5% (50.9%–81.4%). Corresponding specificities were: liquid-based cytology 96.6% (96.0%–97.2%); liquid-based cytology with HPV triage 98.5% (98.0%–98.8%); HPV 92.8% (92.0%–93.6%); and HPV with liquid-based cytology triage 97.7% (97.2%–98.1%). At baseline, HPV testing overlooked five cases of gynecological cancer other than cervical cancer. Five cervical cancers were detected, two had been overlooked at baseline by liquid-based cytology and two by HPV testing Conclusion: HPV screening using DNA amplification is a promising alternative to liquid-based cytology in women age 50 and older, but evaluation of alternative triage methods is warranted. The risk of overlooking cancers needs consideration when replacing liquid-based cytology with HPV testing as a method for primary screening.